Joget TikTok dan Eksistensi Tari Tradisional di Kalangan Siswa: Studi di MAN IC Siak - Armelia, Yuli (el-Khuwailid: Journal of Multidisciplinary Studies, 2025)
The TikTok dance phenomenon has become a widespread trend among the younger generation, including school students. This trend has the potential to influence students' interest in traditional dance, both as a form of appreciation and as an innovation in cultural preservation. This study aims to analyze how TikTok can enhance students' interest in traditional creative dance and the challenges in preserving cultural heritage in the digital era. This research employs a qualitative-descriptive approach with data collection techniques including interviews, observations, and literature studies. The findings indicate that TikTok can serve as an effective medium to introduce traditional dance to the younger generation through creative and interactive content. Data show an increase in students' interest in traditional dance from 35% before using TikTok to 65% after being exposed to traditional dance content on the platform. However, challenges arise in maintaining the cultural essence due to modifications and adaptations that align with social media formats. The study implies that social media can be leveraged as an educational tool for cultural preservation if managed properly. Therefore, active involvement from educators, art communities, and educational policies is necessary to ensure that TikTok’s role in traditional dance is not merely a passing trend but contributes to sustainable cultural preservation.